(untitled) (Research, Society and Development, 2023)
This study had as general objective to present the changes in the psychic health of the woman in the baby blues. This is an integrative bibliographic review of the scientific literature, of a qualitative and exploratory nature, which seeks to analyze studies on baby blues and its implications for women’s mental health. The research was carried out using the SciELO databases, the Regional Portal of the Virtual Health Library (VHL) and the National Library of Medicine National Institutes of Health (PubMed). The final sample consisted of 11 articles indexed in the 3 databases described. The studies fulfilled all the inclusion criteria used in the validation process of the bibliographical research. Postpartum blues is in subgroup F53 of the ICD-10, being clinically marked by an unstable mood pattern, oscillating between happiness and sadness, excessive sensitivity, crying for no reason, restlessness, weakness in concentration, anxiety, irritability and anger. Neglected cases can progress to postpartum depression and psychosis, thus contributing to increased suicidal ideation and consequent rise in maternal mortality rates. It is concluded that there is a scarce production of studies about the impacts of Maternal blues on women’s psychic health. Therefore, further studies involving puerperal women are needed, in order to obtain more information about the psychic repercussions of baby blues in women, as well as to enable the planning of preventive actions even during the gestational period.